Quantifying Bias and Inaccuracy of Upper-Level Aggregation in the Harmonised Index of Consumer Prices for Germany and the Euro Area - Julika Herzberg; Thomas A. Knetsch; Patrick Schwind; Sebastian Weinand (Review of Income and Wealth, 2022)
Current measurement practices of the Harmonised Index of Consumer Prices (HICP) produce an upward bias of about one-ninth of a percentage point in German inflation due to changing consumption being disregarded and preliminary data being used in the compilation of expenditure weights. The statistical uncertainty produced by these sources of mismeasurement can be illustrated by an interdecile range of about one-quarter of a percentage point. The annual updating of the quantity component of the weights, implemented in 2012, has reduced the substitution component, making the disregard of changing consumption virtually a non-issue for the euro area HICP. The measurement of the German HICP is impaired by the extrapolation of expenditure weights. The use of preliminary national accounts data since 2012 has not led to an improvement. This source of mismeasurement is likely to be relevant for the euro area HICP as well but cannot be quantified due to data constraints.
Keywords: 330; inflation measurement; substitution bias; updating of expenditure weights; HICP